THE EFFECT OF ALTERNATE NOSTRIL BREATHING EXERCISE THERAPY ON ELDERLY WITH HYPERTENSION AT RST BHAKTI WIRA TAMTAMA SEMARANG - Putri, Tiara Regina; Sonhaji, Sonhaji (NHM PRESS, 2024)
Background: Management of hypertension is management that sufferers must undergo throughout their lives. Therefore, it is important to take a non-pharmacological therapeutic approach, one of which is using alternate nostril breathing exercise therapy. Aim: to determine the effect of alternate nostril breathing exercise therapy on elderly people with hypertension at RST Bhakti Wira Tamtama Semarang. Method: This type of research uses descriptive case studies. The subjects of this writing are elderly people with hypertension, with the focus of studying alternate nostril breathing exercise therapy in elderly people with hypertension to determine the effectiveness of therapy in improving health. The instruments used include the SOP for Alternate Nostril Breathing Exercise Therapy and a blood pressure measurement observation sheet. Data collection was carried out by interviews, observation and documentation. The process of analyzing and presenting data uses data collection techniques, data reduction, data presentation and conclusions. Results: The author took the problem of acute pain nursing, disturbed sleep patterns and ineffective health management because after conducting an assessment, subjective data was found that both respondents experienced signs of hypertension such as headaches and dizziness. The results of blood pressure measurements showed a decrease after implementing Alternate Nostril Breathing Exercise Therapy using SOPs, leaflets and blood pressure measurement observation sheets. The evaluation found that both respondents experienced a decrease in blood pressure and decreased symptoms of dizziness or headache after being given therapy for 3 days. Conclusion: So it is proven that there is a decrease in blood pressure after the Alternate Nostril Breathing Exercise Therapy intervention